Feasibility study of establishing an integrated organic waste management facility in Singapore - Tan, Sock Ngee. (2008)
The objectives of this dissertation project were to look into eays of making these wastes into useful end product and increasing their useful lifespan, hence ligthening the social and environmental cost on our society.